Left jackknife position: a novel position for laparoscopic hepatectomy - Jian-Cong Chen (Chinese Journal of Cancer, 2017)
Abstract Background Laparoscopic hepatectomy for hepatocellular carcinoma (HCC) located in segment VI, VII, or VIII of the liver is usually difficult because of poor operative exposure, due to the unique anatomical structure. In this study, we evaluated the practice of laparoscopic hepatectomy with the left jackknife position for patients with HCC located in segment VI, VII, or VIII. Methods A total of 10 patients were enrolled to undergo laparoscopic hepatectomy with the left jackknife position. Tumors located in segment VI, VII, or VIII were assessed by preoperative dynamic computed tomography or magnetic resonance imaging. Operation time, intraoperative blood loss, postoperative fasting time, postoperative drainage time, major postoperative complications, and duration of postoperative hospital stay were recorded. Results All surgeries were successfully completed. None of the patients required conversion to open surgery during the procedure, and no serious postoperative complications were observed. The median tumor size was 31 mm (range 23–41 mm) in diameter, the mean operation time was 166 ± 38 min, the mean intraoperative blood loss was 220 ± 135 mL, and the median postoperative hospital stay was 4 days (range 2–7 days). Conclusions For HCC located in segment VI, VII, or VIII, laparoscopic hepatectomy with this novel position—the left jackknife position—is safe and effective during tumor resection by exposing a sufficient operating field. Trial registration ClinicalTrials.gov ID: NCT02809287